Parametric nonlinear singular Dirichlet problems. (February 2019) - Papageorgiou, Nikolaos S.; Vetro, Calogero; Vetro, Francesca
Abstract: We consider a nonlinear parametric Dirichlet problem driven by the p -Laplacian and a reaction which exhibits the competing effects of a singular term and of a resonant perturbation. Using variational methods together with suitable truncation and comparison techniques, we prove a bifurcation-type theorem describing the dependence on the parameter of the set of positive solutions.